Effect of Wood Vinegar Substitutes on Acetic Acid for Coagulating Natural Para Rubber Sheets during the Drying Process - Wachara Kalasee; Panya Dangwilailux (My University, 2021)
The coagulating properties of wood vinegar from para rubber wood, bamboo, and coconut shell used as a substitute for acetic acid in the production process of natural rubber (NR) sheets were investigated and considered. For the dirt and volatile content, the tensile strength at break, the percentage of elongation at break, and the 300% modulus, the results showed that the types of wood vinegar coagulants were not significantly different from acetic acid. However, the Mooney viscosity and plasticity retention index (PRI) properties were significantly different from those of acetic acid. The NR sheet temperature increased rapidly during the first hour after the drying process started due to heat transfer from the hot air. Afterward, the temperature of the NR sheet samples began to stabilize. When the drying process started, the drying temperature was increased, so the trend was reducing the drying time. For the yellowness index (YI) value, the increase in the YI value was related to the type of coagulating material, the increase in the airspeed, and the drying temperature. The dried sheet samples using para rubber wood vinegar as the coagulating material had a color value at the same level as acetic acid and the referent. However, the bamboo and coconut shell wood vinegars were at a lower level. In comparing the YI value data between the experimental results and prediction values, the second-degree model had a better fit in prediction than the zero-degree and first-degree models. This result was confirmed by the higher mean of the coefficient of determination. The dried sheet product coagulated by using wood vinegar had fungus growth prior to supplying it to the customer.
Keywords: Mooney viscosity; Lignin and Wood Chemistry